2017
DOI: 10.1002/aelm.201600468
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electronic Properties of Two‐Dimensional Transition Metal Dichalcogenides by Introducing Mirror Twin Boundaries

Abstract: Grain boundaries in 2D materials can have marked influence on the material properties. The effects can be not only detrimental, but also beneficial in transition metal dichalcogenides (TMDs), so that controlling the density and type of the boundaries in these systems should be important for engineering their properties. However, this is often possibly only during the growth stage. Molybdenum and tungsten dichalcogenides feature a particular set of 60° mirror twin boundaries, which are reported to occur upon me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 55 publications
9
112
0
Order By: Relevance
“…[56] It has to be noted, however, that the amount of edges and defects is quite low in our model ultrathin films and their electrochemistry is ruled mainly by the intrinsic activity of the basal plane. Therefore, the relatively high chemical activity observed in our MoTe 2 samples is likely associated with the presence of the high density of the metallic twin boundaries in our MBE-grown films, which, on the one hand, also improves the electronic transfer capability of the films, [10,45,58] and as we discuss below may also possess special chemical properties. Moreover, these boundaries are 6-7 times denser in MoTe 2 than MoSe 2 (see Figure S2, Supporting Information).…”
Section: Doi: 101002/aenm201800031mentioning
confidence: 99%
See 3 more Smart Citations
“…[56] It has to be noted, however, that the amount of edges and defects is quite low in our model ultrathin films and their electrochemistry is ruled mainly by the intrinsic activity of the basal plane. Therefore, the relatively high chemical activity observed in our MoTe 2 samples is likely associated with the presence of the high density of the metallic twin boundaries in our MBE-grown films, which, on the one hand, also improves the electronic transfer capability of the films, [10,45,58] and as we discuss below may also possess special chemical properties. Moreover, these boundaries are 6-7 times denser in MoTe 2 than MoSe 2 (see Figure S2, Supporting Information).…”
Section: Doi: 101002/aenm201800031mentioning
confidence: 99%
“…[58] These defects can be observed in several types of chalcogenides and can be obtained using several approaches (direct synthesis by MBE or electron beam bombardment or vacuum annealing). [44,58] Their special electronic structure and versatile geometry made them quite interesting to impart TMCs at the nano-or macroscale, [60] with special functional properties such as metallic conductions and unprecedented chemical activity. For the first time, we demonstrated their potential for boosting the HER activity in tellurides, however their presence in several chalcogenides [61][62][63] suggests that the same effect can be reproduced on several other materials.…”
Section: Doi: 101002/aenm201800031mentioning
confidence: 99%
See 2 more Smart Citations
“…Their structures were unambiguously determined by transmission electron microscopy [21][22][23], and density functional theory invariably predicted the MTBs to host one-dimensional, metallic states [24][25][26][27] that are protected through the large band gap of approximately 2 eV in the surrounding 2D-layer. Intense research yielded partly conflicting results regarding the electronic structure of a specific MTB in a monolayer of MoSe 2 resting on a van der Waals substrate [19,28,29], namely the 4|4P MTB consisting of 4-fold rings sharing a point at the chalcogene site [24,30]. By using room temperature as well as low-temperature (4K) STM and STS, Liu et al [28] found a quantum well state emerging from the finite length of the interpenetrating MTBs.…”
Section: Introductionmentioning
confidence: 99%